Índice de desenvolvimento sustentável do município de Foz do Iguaçu - Corrêa, Ricardo Antonio (2010)
The development of a sustainable development index to Foz do Iguaçu is an important evaluative measure of the degree of development of this municipality located in the extreme west of Paraná State, in the tri-border region formed by Brazil, Argentina and Paraguay. In this local park is one of the greatest wonders of nature, the waterfalls of the Iguazu River surrounded by lush vegetation protected under the aegis of a national park of the same name. It is also on the opposite side, north of the city, a monumental work of human engineering, the Itaipu Dam, the largest generator of hydroelectric power on the planet. These elements eventually configure a single specific region that deserves to be studied, especially in light of the concept of sustainable development. Accordingly, we chose to measure this development by calculating an overall summary and that can measure the level of local sustainability. The methodology used was the Dashboard of Sustainability, coupled with theoretical extracted from the work of Ignacy Sachs so that it can better understand the social, economic, political and environmental factors that helped shape Foz do Iguacu. The results characterize the performance of sustainable development as "regular", these values are associated with the favorable performances of the environmental, performance presented by social, economic and institutional express concern, requiring public actions designed to resolve the issues raised.